Fiddler on the roof - Jewison, Norman 1926-.; Mirisch Company (Sta. Monica, Calif. Metro-Goldwyn-Mayer Studios and Norman Jewison, 1971)
Tevye is a poor Jewish milkman with five unmarried daughters to support in a village in Czarist Russia. With a sharp tongued wife at home and growing anti-Semitism in the village, Tevye talks to God about his troubles. His people's traditions keep him strong when his existence is as precariously balanced as a fiddler on the roof.
Disc 1: 58 min. -- disc 2: 53 min. -- disc 3: 1 hr., 8 min.
Based on the stageplay Fiddler on the roof ; adapted from Sholem Aleichem stories by special arrangement with Arnold Perl.
Printed and exclusively distributed in the Philippines by Viva Video, Inc.
VCD.
Golden Globe Award for Best Motion Picture (Musical/Comedy), 1972.
Story by Joseph Stein ; screenplay by Joseph Stein ; produced and directed by Norman Jewison ; Isaac Stern, soloist.
Topol, Norma Crane, Leonard Frey, Molly Picon, Paul Mann.
Keywords: Jews -- Social life and customs -- Ukraine -- Drama; Feature films; Musical films; Film adaptations